(untitled) (The Peerian Journal, 2022)
In this project, we use an Arduino Uno to build an autonomous "follow me" cooler. The robot cooler connects to a smartphone via Bluetooth and uses GPS to navigate. All the electronics will be contained in the base so that other objects can be carried as well.